Much ado about nothing - Shakespeare, William 1564-1616; Doyle, Patrick 1953- (MGM Home Entertainment, 2003)
With his wedding a week away, Claudio can't wait to marry the beautiful young Hero. To distract him, his best friend Don Pedro devises mischief: a romantic trap for the sharp-tongued Beatrice and the man she loves to hate, Benedick. Their amusement is almost spoiled by the jealous scheming of Don John, but love and laughter prevail when the local constable unwittingly exposes the plot--and all the trouble proves to be much ado about nothing (111 min.).
Bildformat: 1.85:1 (16:9 widescreen)
Orig.: USA, Großbritannien 1993
Enth. Making of "Much ado" featurette
Keywords: Shakespeare, William -- 1564-1616 -- Much ado about nothing; Amor - Teatro; Love - Drama; Man-woman relationship - Drama; Relaciones hombre-mujer - Teatro; Love -- Drama; Man-woman relationships -- Drama; Verschwörung; Abweisung; Verfilmung; Brautwerbung; Film; Feature films; Film adaptations; Romantic comedy films; Video recordings for the hearing impaired; Adaptation - Feature; Comedy - Feature; Comedy films; Romance - Feature